Financial Feasibility Study for The Construction of The Pulo Gebang–Joglo Light Rail Transit (LRT) Project - Ariyanti, Adi; Al Rasyid Lubis, Harun; Karsaman, Rudy Hermawan (Riviera Publishing, 2024)
The DKI Jakarta Regional Government is evaluating a rail Public-Private Partnership (PPP) proposal for the Pulo Gebang-Joglo Light Rail Transit (LRT) under the Unsolicited Local Government and Business Entity Cooperation (KPDBU) scheme. This thesis examines the project's feasibility, focusing on financial and risk aspects. The proposal is currently under review by the DKI Jakarta Provincial Government. Passenger forecasts include pessimistic, moderate, and optimistic scenarios to estimate potential revenue. Investment costs (capex) and service revenue are calculated for a 30-year concession period. A financial feasibility study, assuming 4% inflation and a 9.15% benchmark interest rate, utilizes Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and payback period metrics. The project is deemed financially viable under the Availability Payment (AP) scheme, yielding an NPV of Rp14.23 trillion, an IRR of 11.77%, and a PI of 1.035. The payback period is projected at twelve years, with annual AP payments of Rp1.94 trillion over the concession period. Risk analysis identified 16 risks across six categories, with 44% classified as very high, 38% high, and 19% medium. Financial aspects based on VAT Regulation No. 2 of 2020 scored 52.5%, the PPP aspect 41.7%, and government support/government guarantees 50%. Despite its financial feasibility, the unsolicited KPDBU proposal requires further refinement, particularly regarding AP financing and tariff revenue accountability. Separate audit mechanisms are needed to ensure transparency and alignment with government regulations.